A new cluster of rhabdovirus detected in field-caught sand flies (Diptera: Psychodidae: Phlebotominae) collected from southern Thailand - Atchara Phumee (BMC, 2021)
Abstract Background The distribution of phlebotomine sand flies is changing rapidly due to climate change. This issue has implications for the epidemiology of sand fly-borne diseases, especially sand fly-associated viruses. Few studies concerning sand fly-associated viruses have been conducted in Thailand. Therefore, this study aimed to perform a molecular survey of groups of pathogenic RNA viruses belonging to the Orbivirus, Phlebovirus, and Flavivirus genera and family Rhabdoviridae in sand fly samples collected from southern Thailand. Methods Sand flies were collected at two locations in Trang and Songkhla provinces of southern Thailand, and individual sand fly samples were processed for species identification and virus detection. The Orbivirus, Phlebovirus, and Flavivirus genera and family Rhabdoviridae molecular determination was performed by RT-PCR, and positive samples were identified by cloning and sequencing, cell culture inoculation, and phylogenetic analysis. Results The results presented in this study were based on the analysis of a total of 331 female sand flies. This molecular study revealed evidence of Rhabdoviridae family virus presence in Phlebotomus papatasi (3/331, 0.9%). The findings demonstrated a new cluster of rhabdovirus that was closely related to Bactrocera dorsalis sigmavirus strain BDSV.abc5 and the lineages of insect-specific Rhabdoviridae. In addition, the Bayesian tree suggested that the common ancestor of this group was the dimarhabdovirus clade. It was assumed that the virus may have switched hosts during its evolution. However, the detection of Orbivirus, Phlebovirus, and Flavivirus genera using specific primers for RT-PCR was negative in the collected sand flies. Conclusions There is limited knowledge on the genetic diversity and ecology of Rhabdoviridae in Thailand. This is the first data regarding the circulation of Rhabdoviridae in Ph. papatasi from Thailand. We found a new cluster of rhabdoviruses that was close to the new B. dorsalis sigmavirus. It is possible that there is a great deal of diversity in this family yet to be discovered, and a more extensive survey for new rhabdoviruses may uncover viruses from a wide diversity of host taxa and broaden our understanding of the relationships among the Rhabdoviridae. Graphical abstract